Analysis of Question Sentences on the Novels Kulit Kerang Si Penyelamat as an Alterative to Creating Learning Media - Ermawati, Eli; Wardana, Deni; Widjojoko, Widjojoko (Universitas Pendidikan Indonesia Kampus Serang, 2021)
An interrogative sentence is a sentence that is used to obtain information in the form of answers from his communication friends. The learning medium used in delivering question sentences on interview text writing materials is usually only from books and examples of interview text, other sources that can be used are novels. This study aims to analyze the use of question sentences in the novel of Kulit Kerang Si Penyelamat to then be made into a learning medium to write interview text. This study used a qualitative approach of content analysis method. Based on the results of the analysis, there are 112 question sentences found in the novel Kulit Kerang Si Penyelamat, 62 of them are interrogative sentences that use the question word and another 50 sentences without using the question word. The question word that uses the question word is characterized by the presence of the question word â€œwhatâ€, â€œwhoâ€, â€œwhenâ€, â€œwhereâ€, â€œwhyâ€, and â€œhowâ€ and the sentence of the question without using the question word is marked by the presence of a question mark (?). There is a word â€œyetâ€, and there is a tag â€œrightâ€ at the end of the sentence. From the results of the analysis obtained the animation video learning media for the material of writing the interview text of fourth-grade elementary school students